Economics for Policy Makers : A Guide for Non-Economists - Rinaldi, Gustavo (Abingdon, Oxon : Routledge, 2019)
Certain key economic decisions taken by organizations and indeed countries are often not made by economists but by businessmen, trade unionists, politicians and policy-makers. Those who employ people, those who represent workers, those who make laws and those who elect them need economics but may have little time or desire to study it. This book makes economics easily available to everyone. The author's use of simple language and avoidance of technical jargon provides non-economists with a better understanding of economic reasoning and the tools "to know and to decide". The author achieves this through introducing key concepts in short presentations and arming the reader with selected press articles and recent research using these concepts. An analysis of these demonstrates how a general concept can be derived from a specific context and highlighted questions provide the basis for further debate. The reader can then focus on the parts most relevant to their own needs. This book will have great appeal to employers, trade unionists and public officials attending courses organized by international institutions, professional training providers, as well as graduate students of courses where economics is an important element, especially in relation to its policy implications. Finally, it is invaluable for anybody who has wanted to learn the basics of practical economics but has been deterred by its technicalities.
OCLC-licensed vendor bibliographic record.
Keywords: Economics; Economic policy; Economic forecasting; BUSINESS & ECONOMICS / Economics / General; BUSINESS & ECONOMICS / Reference